Zwierzęce cmentarze jako miejsca performansu kulturowego - Kwiecień, Arkadiusz (Zoophilologica. Polish Journal of Animal Studies, 2019)
Using the tools and definitions provided by performance studies (Richard Schechner, Jon McKenzie, Erika Fischer-Lichte, Małgorzata Sugiera, Dariusz Kosiński and others) as well as by newer post-human turn (Ewa Domańska) the author analyses the phenomenon of burying domestic animals on sites located on the outskirts of populated areas (resembling the old cholera graveyards). Animal burial sites are denied the term ‘cemetery’ by official legislation which reserves the notion only for human necropolises. Almost every suggestion of establishing an animal cemetery in Poland is met with highly emotional reactions and protests. Itself being acts of social performance, the protests evoke burial as a social performance art, where the community participates in an event based on a standard Christian funeral ceremony. The unstandardized character of the animal’s funeral challenges this view. In the act of animal burial an oppressive gaze of a society is juxtaposed with an intimate one. The confrontation becomes a chance for the society for a self-reflection and transformation. Hence one may prove that the animal burials have a significant performative power and can have social and cultural impact.